2018
DOI: 10.3390/ijms19072099
|View full text |Cite
|
Sign up to set email alerts
|

B Regulatory Cells: Players in Pregnancy and Early Life

Abstract: Pregnancy and early infancy represent two very particular immunological states. During pregnancy, the haploidentical fetus and the pregnant women develop tolerance mechanisms to avoid rejection; then, just after birth, the neonatal immune system must modulate the transition from the virtually sterile but haploidentical uterus to a world full of antigens and the rapid microbial colonization of the mucosa. B regulatory (Breg) cells are a recently discovered B cell subset thought to play a pivotal role in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 137 publications
(247 reference statements)
0
29
0
1
Order By: Relevance
“…B cells play a broader, yet unclear, role in maintaining or disrupting normal pregnancies. 36 Recent advances in studies of regulatory B-cell populations indicate shifting dynamics during pregnancy. 36 That this could affect repopulation of specific B-cell subsets after prepregnancy B-cell depletion seems plausible, but whether this would result in improved or worsened pregnancy outcomes remains murky.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B cells play a broader, yet unclear, role in maintaining or disrupting normal pregnancies. 36 Recent advances in studies of regulatory B-cell populations indicate shifting dynamics during pregnancy. 36 That this could affect repopulation of specific B-cell subsets after prepregnancy B-cell depletion seems plausible, but whether this would result in improved or worsened pregnancy outcomes remains murky.…”
Section: Discussionmentioning
confidence: 99%
“…36 Recent advances in studies of regulatory B-cell populations indicate shifting dynamics during pregnancy. 36 That this could affect repopulation of specific B-cell subsets after prepregnancy B-cell depletion seems plausible, but whether this would result in improved or worsened pregnancy outcomes remains murky. Future studies examining immunoglobulin levels, B-cell subset repopulation, and pregnancy and neonatal outcomes are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the old concept that B cells participate in fetalmaternal immune tolerance via attenuating B-cell capabilities characterized by diminished immune responses and reduced auto-antibodies, recent studies have demonstrated that the increased regulatory B cells (Bregs) play an indispensable role in preventing semi-allogeneic rejection and promoting a stable tolerant microenvironment during normal pregnancy [75][76][77][78] . Of particular note, Tfr cells not only regulate GC reaction by inhibiting B-cell maturation, differentiation and antibody production, but also provide IL-10 for Breg-cell proliferation and differentiation 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in immunologic function between young children and adults likely contribute to the increased susceptibility of children to influenza virus infection. The immune system of young children is characterized by a higher frequency of naïve antigen-specific cells [106,107]. This population also tends to have an overall higher number of circulating T and B cells that decreases drastically by six years of age [108].…”
Section: The Pediatric Immune System Is Different Than That Of the Adultmentioning
confidence: 99%